SISTEM INFORMASI E-RETENSI REKAM MEDIS (Studi Kasus: RSAU LANUD SULAIMAN BANDUNG) - Alfany Nurulita (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
The Air Force Hospital (RSAU) Sulaiman Air Base is the implementing unit for the Sulaiman Air Base, Bandung Regency, which is directly under the commander of the Sulaiman Air Force Base who is in charge of carrying out health activities required by every Indonesian Air Force operation. Therefore, the health services provided must be in the best possible form, including managing medical records. However, several issues were discovered, including the processing of medical record retention activities which were still done manually, which hampered the destruction process and resulted in the accumulation of medical records in the filling room. This study aims to change the existing manual system into a computerized system, by designing a web-based medical record retention information system. The PHP programming language, CodeIgniter Framework, and MySQL database management are used to create the system. Using a qualitative research method with a descriptive approach, with data collection procedures including literature review, observation, and interviews. Waterfall method is used in software development, while Data Flow Diagrams are used in information system design. It's intended that the design of this information system will make it easier for hospital employees to keep track of medical records, preventing medical records from pilling up.